Regional Anaesthesia with Non Invasive Ventilation and Conscious Sedation: An Alternative to General Anaesthesia in Morbidly Obese Patients with Obstructive Sleep Apnea in Retrograde Intrarenal Surgery - Ankit Agarwal; Pragya Varshney; Alok Padhee; Ravi Chaudhary (Archives of Anesthesia and Critical Care, 2023)
Obstructive sleep apnea(OSA) is a syndrome characterized by obstruction in the upper airway during sleep. OSA patients undergoing procedures under GA are at increased risk for hypoxemia, pneumonia, difficult intubation, atelactasis, myocardial infarction making it a challenge for anesthesiologist. Retrograde intrarenal surgery(RIRS) is normally performed under GA to prevent respiratory embaracement. There are very few studies focusing on Regional anesthesia in RIRS procedure. A Sixty-three-year-old male known case of morbid obesity (BMI- 35 kg/meter square), OSA (on CPAP support at night) presented with left renal pelvis calculus, STOP BANG score (=5) therefore making it a case of difficult airway. Respiratory discomfort improved at 30-35-degree head up due to existing OSA considering the severe OSA and anticipated difficult airway, the surgery was planned under Lumbar subarachnoid block with preparation for management of difficult airway if conversion to GA required. 3 ml of 0.5 percent Bupivacaine heavy and 25 mcg fentanyl injected into subarachnoid space. T6 level block acheived after 3 minutes. The patient was put on his home CPAP machine with 5cm H2O PEEP. The patient was maintained on sponatneous ventilation and monitored using Etco2 at aliquot of 1mg midazolam given to mimic natural sleep pattern. The surgery was uneventful and the risk of induction of GA and difficult intubation was succesfully avoided. Patient with regional anaesthesia who are prone to converted to GA due to multiple risk factors, i.e., OSA with anticipated difficult airway can create a chaotic situation. So as a preliminary step NIV can be used, and along with it, mild sedation can be supplemented to improve acceptance and to avoid asynchrony. In this case NIV was used as a preemptive ventilation strategy even before actual requirement of BiPAP by mimicing the natural sleep pattern and make patient comfortable while a smooth conductance of the procedure.